Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Tema Bumiku Melalui Model Discovery Learning di kelas VI UPTD SDN 02 Taeh Baruah Tahun 2022 - Sutra Aryenti (Departement of Mathematics Education, 2022)
The purpose of this study is to describe the Indonesian language using a scientific approach to the discovery learning model to improve student learning outcomes in Indonesian subjects in class VI UPTD SD Negeri 02 Taeh Baruah. This type of research is Classroom Action Research. The research was carried out based on classroom action research steps with two cycles starting from the planning, implementation, observation and reflection stages. Research data in the form of test results, learning observations, field notes, and documentation of each learning improvement action. The source of research data is the process of learning activities. The data were obtained from the research subjects, namely teachers and students of class VI, totaling 25 people, which was held from January to March 2022. The results of the research data analysis showed that the use of a scientific approach to the discovery learning model could improve student learning outcomes. This is evident from the increase in student learning outcomes in terms of knowledge and skills. The learning outcomes of the knowledge aspect have increased from 68.00 in pre-cycle activities to 74.00 in the first cycle, increasing again to 91.20 in the second cycle with an increase of 23.20. The learning outcomes of skills aspect obtained an average of 67.60 in the pre-cycle, increasing to 75.20 in the first cycle and increasing again to 97.60 in the second cycle with an increase of 30.00. Based on the results of this study, the conclusions of the study using a scientific approach to the discovery learning model in Indonesian subjects need to be applied and developed in order to improve the quality of education.